2016
DOI: 10.1088/1751-8113/49/46/465202
|View full text |Cite
|
Sign up to set email alerts
|

Scattering theory without large-distance asymptotics in arbitrary dimensions

Abstract: In conventional scattering theory, by large-distance asymptotics, at the cost of losing the information of the distance between target and observer, one imposes a largedistance asymptotics to achieve a scattering wave function which can be represented explicitly by a scattering phase shift. In this paper, without large-distance asymptotics, we establish an arbitrary-dimensional scattering theory. Arbitrary-dimensional scattering wave functions, scattering boundary conditions, cross sections, and phase shifts a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…As a result, information about the angular current contributions [25], and the distance between target and observer is lost in this analysis. In reports by Dai et al, [26,27] it has been shown that a rigorous scattering treatment without the asymptotic approximations introduces a modification factor to the scattering amplitude, and an additional phase factor to the scattered wavefunction. Hence, our first aim is to formulate a framework to obtain the scattering properties without applying asymptotic BCs.…”
Section: Planewave Sourcementioning
confidence: 99%
“…As a result, information about the angular current contributions [25], and the distance between target and observer is lost in this analysis. In reports by Dai et al, [26,27] it has been shown that a rigorous scattering treatment without the asymptotic approximations introduces a modification factor to the scattering amplitude, and an additional phase factor to the scattered wavefunction. Hence, our first aim is to formulate a framework to obtain the scattering properties without applying asymptotic BCs.…”
Section: Planewave Sourcementioning
confidence: 99%
“…(5.15) still diverges. However, the divergence can be removed by a renormalization procedure [12]. We will illustrate such a renormalization procedure by taking the Cauchy distribution as an example in section 6.2.5.…”
Section: Probability One-loop Effective Actionmentioning
confidence: 99%
“…The phase shift δ l . For scattering of a plane wave by a spherically symmetric target, the solution of equation (1.1) can be written as a linear combination of the spherical Hankel function [3,6]…”
Section: Scattering Phase Shiftmentioning
confidence: 99%
“…Recently, a rigorous scattering theory without large-distance asymptotics in quantum mechanics is developed [5,6]. In this scattering theory, the information of the distance between the target and the observer is taken into account, since there is no large-distance asymptotic approximation.…”
Section: Introductionmentioning
confidence: 99%